Moral Genealogy of Michel Foucault in the Ad Hominem Argument in the Terminology of 'Cicak' and 'Buaya' - Teguh Hidayatul Rachmad; Yohanes Probo Dwi Sasongko (Jurnal Komunikasi, 2023)
The feud that occurred between government agencies, in this case involving the Corruption Eradication Commission (KPK), and government agencies, in this case the National Police, became an ongoing problem that could be considered as a whole. The terminology regarding the KPK and Polri cases, which are synonymous with the term lizard and crocodile, is a separate understanding that needs attention. Public perception of the case varies. There is support for the KPK, but there are also those who justify the treatment of the Police themselves in looking at this case. Foucault's moral genealogy uses ad hominem arguments as the basis for forming his genealogy, used to expose the understanding of lizards and crocodiles. An understanding that society takes for granted as truth and morality. In the genealogy, Foucault sees that in the context of the lizard and the crocodile, there is a kind of power that is to be played and used for a certain interest. There is a purpose to be sought from such a political situation and condition. So, looking at the context of lizards and crocodiles in ad hominem studies is one of the studies of message communication. Political communication that wants to open up new understandings of the logic of human thinking as a whole.